تدبير التهاب المرارة الحادّ الحصوي بالتنظير - علي ماجد; محمّد أسامة (Latakia University Journal -Medical Sciences Series, 2016)
شملت الدراسة (163) حالة استئصال مرارة بالتنظير باستطباب التهاب مرارة حادّ حصوي، في الفترة من 1/1/2010 ولغاية 31/12/2013 وذلك في قسم الجراحة بمشفى الأسد الجامعي باللاذقية. كانت نسبة الذكور (24.5 %) والإناث (75.5 %) ونسبة الإناث إلى الذكور (1:3.08). أغلب مرضى دراستنا (53.4 %) كانوا بعمر بين (21-40) سنة. أكثر الأعراض توارداً في دراستنا كانت الألم (92.6 %)، والحمّى (74.8 %)، والغثيان والقياء (72.4 %). أجري إيكو البطن عند المرضى جميعهم. أكثر المضاعفات أثناء استئصال المرارة بالتنظير كانت تمزّق المرارة وسقوط الحصيّات في البطن (3.7%)، وبعد العمل الجراحي كان التسرّب الصفراوي (8.6 %). نسبة التحويل من الجراحة التنظيرية إلى الجراحة المفتوحة كانت (7.4 %). (50.9 %) من مرضانا أجري لهم التداخل الجراحي خلال الـ 72 ساعة الأولى من الدخول إلى المشفى و(49.1 %) تمّ التداخل الجراحي بعد الـ 72 من الدخول إلى المشفى. متوسّط مدّة العمل الجراحي في دراستنا (72) دقيقة. متوسّط مدّة الإقامة بالمشفى (1.7) يوم. This study included (163) patients admitted to the department of Surgery in Al-Assad university hospital at Lattakia , between 1/1/2010 and 31/12/2013. They all had Laparoscopic cholecystectomy due to acute cholecystolithiasis. The male patients composed (24.5%), and the female patients composed (75.5%) and the ratio of females to males was (1:3.08). In our study the age of most patients (53.4 %) was between (21-40) years. The more frequent clinical features was pain (92.6%) , fever (74.8%) and (nausea + vomiting) (72.4%). Ultrasound abdomen was done in (100%). The most intra – operative complication was perforation of gall bladder and spilled stones (3.7%) and post – operative complication was spilled bile. The conversion rate from Laparoscopic cholecystectomy to open method was (7.4%). cholecystectomy was done in (50.9%) in the first 72 hours of hospitalization and was done in (49.1 %) after the 72 hours of hospitalization. The median operating time was (72) minutes . The mean stay being (1.7) days.